SOURCES FOR THE HISTORY OF BRITISH SPORT IN THE NATIONAL ARCHIVES. Issue 130 (April 2015) - Paley, Ruth
Abstract : The National Archives has catalogued over 100, 000 of the records that it holds as sports related. Because until comparatively recently the majority of these records were created as a by-product of government actions, they are difficult to use systematically. This essay attempts to provide an overview of an otherwise amorphous and eclectic survival of information in order to facilitate and encourage research into the history of British sport.